TAX-EDX: transforming tax education through experiential learning and SMEs engagement - Jamil, Amira; Azmi, Nur Farahiah; Abdullah, Tahirah; Mohamad, Siti Rohana; Muhamad, Siti Fariha (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
Traditional classroom-based tax education is often characterised by passive, theory-driven instruction, which limits students’ engagement and restricts the development of practical skills essential for real-world application. This gap in experiential learning results in a disconnect between academic knowledge and real-world practice, particularly evident among micro-enterprises. Micro-entrepreneurs, especially those in the Food and Beverage (F&B) sector, often struggle with tax compliance due to limited awareness, financial constraints, and the complexity of tax regulations. Despite the introduction of e-invoicing to streamline financial reporting, its adoption remains low among SMEs. In response to these issues, this research introduces TAX-EdX, an experiential learning framework designed to enhance tax education by bridging theoretical knowledge with real-world practice. TAX-EdX immerses students in a structured, scaffolded learning approach, allowing them to engage directly with micro-entrepreneurs to assess tax compliance behaviour and e-invoicing adoption. The framework leverages experiential learning theory and scaffolding theory to guide students through structured support, including guided interviews, data analysis, and consultation-based learning. 90 undergraduate students enrolled in the Taxation I course were divided into 18 groups of five and tasked with conducting interviews and providing tax compliance consultations to micro-entrepreneurs in the sector. The research adopts a qualitative, problem-based learning approach, where students engage in real-world problem-solving, consulting elements, and structured mentorship to develop a deeper understanding of taxation. By incorporating experiential learning techniques and scaffolded guidance, TAX-EdX fosters a hands-on learning environment while providing SMEs with actionable insights to improve compliance. This study highlights the innovation and impact of TAX-EdX in enhancing tax literacy, increasing SME engagement, and informing tax policy reforms through empirical findings.